Religious Textual in Mahwy’s Poems with Holy Quran’s Example - Mohammed Omer Ibrahim; Abdullah Yassin Amedi (QALAAI ZANIST JOURNAL, 2022)
(Religious textual in Mahwy’s poems with Holy Quran’s example) is the title of the research that is an academic work .To show religious texts specially Holy Quran, it shows clearly in his poems .Also this research consists two main parts in the first part in a theoretical way talks about religious textual , concepts and definition of religious textual and types of religious textual ) in the second part of this study in a practical way it talks about the ( some of classical poets who have entered Holy Qurans texts in their poems ) After that it shows Mahwy’s religious textual with Quran’s examples). As a result, in this study, we find that according historical sources, concept of religious textual for the first time emerged in critical European literature and its leaders were (Mikhail Bakhtin, Golia kritiva and Rolan Bart) But in Kurdish literature religious textual emerged in. But for the first time called like literally thief , religious literature was an important source of poet’s knowledge the poets one of those who have great religious knowledge about Quran and interpretation) so it was an important source for creating religious textual . In the End of this Study, it shows the result of this research also those sources that relied on.